Answer:
B. x ≥ 3 or x ≤ −2
Step-by-step explanation:
Inequalities
Solve the inequality:
[tex]x^2-x\ge 6[/tex]
Subtracting 6:
[tex]x^2-x-6\ge 0[/tex]
Factoring:
(x-3)(x+2) ≥ 0
We have a product that must be greater or equal to 0. This can only happen if:
x - 3 ≥ 0 and x + 2 ≥ 0
Or:
x - 3 ≤ 0 and x + 2 ≤ 0
The first couple of conditions yields to:
x ≥ 3 and x ≥ -2
Which lead to the solution
x ≥ 3 [1]
The second couple of conditions yields to:
x ≤ 3 and x ≤ -2
Which lead to the solution
x ≤ -2 [2]
The final solution is [1] or [2]:
Answer:
B. x ≥ 3 or x ≤ −2